Multi-modal imaging of the cementitious carbonation front: Evidence for pore refinement - Sudharsan Rathnakumar; Nishant Garg (Journal of CO2 Utilization)
Cementitious carbonation is an important phenomenon considering its dual implications on durability (carbonation-induced steel corrosion) and sustainability (CO2 mineralization in carbonatable binders). Currently, there is strong interest in understanding the nature of the carbonation front and resolving microstructural changes that happen upon carbonation. In this study, we shed light on these issues by adopting a multi-modal imaging approach wherein we deploy three complementary methods on the same specimen that has undergone carbonation: laser profilometry, contact angle goniometry, and Raman imaging. Firstly, we find that irrespective of the technique deployed, the carbonation front is non-planar, and its width can be on the order of a few millimeters. Secondly, the intersection region of calcite and portlandite mineral maps roughly correlates with the front as mapped from imaging methods. Thirdly, and finally, the carbonated region of hydrated cement samples seems to have undergone measurable pore refinement. Thus, we demonstrate the efficacy of multi-modal imaging in improving our understanding of cementitious carbonation front.